FlexED8: the first member of a fast and flexible sample‐changer family for macromolecular crystallography. Issue 10 (10th October 2017) - Papp, Gergely; Felisaz, Franck; Sorez, Clement; Lopez-Marrero, Marcos; Janocha, Robert; Manjasetty, Babu; Gobbo, Alexandre; Belrhali, Hassan; Bowler, Matthew W.; Cipriani, Florent
Abstract : A sample changer based on a six‐axis industrial robot and a new sample‐storage dewar with an ice‐cleaning feature have been developed to open automated X‐ray crystallography beamlines to new sample‐holder models, such as miniSPINE and NewPin, while remaining compatible with the widespread SPINE sample‐holder standard. Abstract : Automated sample changers are now standard equipment for modern macromolecular crystallography synchrotron beamlines. Nevertheless, most are only compatible with a single type of sample holder and puck. Recent work aimed at reducing sample‐handling efforts and crystal‐alignment times at beamlines has resulted in a new generation of compact and precise sample holders for cryocrystallography: miniSPINE and NewPin [see the companion paper by Papp et al. (2017, Acta Cryst., D73, 829–840)]. With full data collection now possible within seconds at most advanced beamlines, and future fourth‐generation synchrotron sources promising to extract data in a few tens of milliseconds, the time taken to mount and centre a sample is rate‐limiting. In this context, a versatile and fast sample changer, FlexED8, has been developed that is compatible with the highly successful SPINE sample holder and with the miniSPINE and NewPin sample holders. Based on a six‐axis industrial robot, FlexED8 is equipped with a tool changer and includes a novel open sample‐storage dewar with a built‐in ice‐filtering system. With seven versatile puck slots, it can hold up to 112 SPINE sample holders in uni‐pucks, or 252 miniSPINE or NewPin sample holders, with 36 samples per puck. Additionally, a double gripper, compatible with the SPINE sample holders and uni‐pucks, allows a reduction in the sample‐exchange time from 40 s, the typical time with a standard single gripper, to less than 5 s. Computer vision‐based sample‐transfer monitoring, sophisticated error handling and automatic error‐recovery procedures ensure high reliability. The FlexED8 sample changer has been successfully tested under real conditions on a beamline.